Peranan Organisasi Karang Taruna Dalam Pemberdayaan Masyarakat Desa (Suatu Studi Di Desa Tewasen, Desa Pondos, Desa Elusan, Desa Wakan Kecamatan Amurang Barat Kabupaten Minahasa Selatan) - Kawalod, Farra Aprilia; Rorong, Arie Junus; Londa, Very Yohanes (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT : Observe to the problem that faced by young generation, it is necessary to attempt that will help those young generation to solve problems which that attempt need a place to develop and direct them. The implementation of development is a government duty from national to local government with appropriate expertise. Then the implementation will translate to society life especially in counselling such as build an organization that become a place to develop young generation in village. As an example is Karang Taruna that can be a place to accommodating the aspirations and involved young generation to manage. Beside, Karang Taruna also play role as place to grow sense of nationality, develop self potency and social welfare. Research Method : This research using descriptive qualitative approaching method by deep interview to 7 responden, observe and files investigation using additional instruments such as interview guidance list, recorder and stationery. Research results : According the role of Karang Taruna from 4 villages, they haven’t implemented the main role and duty as a organization yet. There were only two villages that have a good implementation , they are Tewasen and Pondos Village while the other two haven’t optimal implementation yet. Karang Taruna of Pondos Village has a good program’s plan but in their role as a government partner in society welfare hasn’t optimal yet while good partnership shown is social life but need more guidance. Elusan and Wakan Village had not an optimal program’s plan, society empowerment and social welfare. Conclution : There are only two Karang Taruna with a good role implementation of society empowerment from four Karang Taruna as an object of this research. They are Karang Taruna of Tewasen and Pondos Village while Karang Taruna of Elusan and Wakan Village haven’t good implementation yet. Keywords : role, Karang Taruna Organization, village society.